2021
DOI: 10.1111/add.15393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of initiation of medications for opioid use disorder on hospitalization outcomes for endocarditis and osteomyelitis in a large private hospital system in the United States, 2014–18

Abstract: Background and Aims Opioid use disorder (OUD) has led to not only increases in overdose deaths, but also increases in endocarditis and osteomyelitis secondary to injection drug use (IDU). We studied the association between initiation of medications for opioid use disorder (MOUD) and treatment outcomes for people with infectious sequelae of IDU and OUD. Design and setting This is a retrospective cohort study reviewing encounters at 143 HCA Healthcare hospitals across 21 states of the United States from 2014 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 49 publications
5
31
0
Order By: Relevance
“…Patients with opioid use disorder are at risk for many infectious conditions in addition to Clostridia, such as endocarditis, Hepatitis C, and HIV infection. In studies of endocarditis patients with opioid use disorder, use of medications for opioid use disorder (MOUD) was associated with a higher rate of receiving gold standard therapy for endocarditis [ 19 ], and lower mortality while actually receiving MOUD, though retention in MOUD programs post-discharge was low [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with opioid use disorder are at risk for many infectious conditions in addition to Clostridia, such as endocarditis, Hepatitis C, and HIV infection. In studies of endocarditis patients with opioid use disorder, use of medications for opioid use disorder (MOUD) was associated with a higher rate of receiving gold standard therapy for endocarditis [ 19 ], and lower mortality while actually receiving MOUD, though retention in MOUD programs post-discharge was low [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…These invasive infections are increasingly common [2][3][4][5][6], and in-hospital initiation of medications for opioid use disorder (MOUD) is both a crucial component of secondary prevention [7][8][9][10][11][12] and the standard of care for treating opioid use disorder [13][14][15][16][17]. While the paper refers to 'initiation of MOUD' having limited effect, the investigators did not actually assess the effect of in-hospital initiation of buprenorphine or methadone maintenance treatment for opioid use disorder; they identified patients receiving either medication for any indication, including for opioid withdrawal [1]. We worry that soft-pedaling this distinction may mislead patients, clinicians and policymakers into thinking that MOUD treatment has relatively little impact in the hospital setting.…”
mentioning
confidence: 99%
“…Unfortunately, dosages of methadone and buprenorphine were not reported in the study; these might have been used as a proxy for providers' intentions to continue these medications long-term. Table 2 shows that only 44 patients (3.1% of the total sample and 16.4% of those who received any dose of MOUD) were continued on MOUD at discharge, indicating that most patients only received these medications short-term, probably to relieve symptoms of opioid withdrawal [1]. As the authors note, a randomized controlled trial has shown continuation of MOUD after in-hospital initiation is much more effective at engaging patients in treatment compared to simply outpatient referral after withdrawal management [19].…”
mentioning
confidence: 99%
See 2 more Smart Citations